Directional Polarized Light Emission from Thin‐Film Light‐Emitting Diodes. Issue 9 (29th January 2021) - Fu, Xiangyu; Mehta, Yash; Chen, Yi‐An; Lei, Lei; Zhu, Liping; Barange, Nilesh; Dong, Qi; Yin, Shichen; Mendes, Juliana; He, Siliang; Gogusetti, Renuka; Chang, Chih‐Hao; et al.
Abstract: Light‐emitting diodes (LEDs) with directional and polarized light emission have many photonic applications, and beam shaping of these devices is fundamentally challenging because they are Lambertian light sources. In this work, using organic and perovskite LEDs (PeLEDs) for demonstrations, by selectively diffracting the transverse electric (TE) waveguide mode while suppressing other optical modes in a nanostructured LED, the authors first demonstrate highly directional light emission from a full‐area organic LED with a small divergence angle less than 3° and a TE to transverse magnetic (TM) polarization extinction ratio of 13. The highly selective diffraction of only the TE waveguide mode is possible due to the planarization of the device stack by thermal evaporation and solution processing. Using this strategy, directional and polarized emission from a perovskite LED having a current efficiency 2.6 times compared to the reference planar device is further demonstrated. This large enhancement in efficiency in the PeLED is attributed to a larger contribution from the TE waveguide mode resulting from the high refractive index in perovskite materials. Abstract : Highly directional and polarized light emission is demonstrated in thin‐film light‐emitting diodes (LEDs) by suppressing the background emission and extracting only the transverse electric (TE) waveguide mode. It is found that the TE waveguide mode increases with the refractive index of the emitting layer and a 2.6 times higher current efficiency is achieved in a perovskite LED.